Exploring Vocational School English Teachers’ Technological Knowledge in Bukittinggi City - Ega Giana; Aryuliva Adnan (Journal of English Language Teaching, 2022)
The development of technology in the 21st century impacts all aspects of life, one of which is the field of education. Therefore, the teachers must be able to master technologies that can support learning so that they become 21st-century learning characters. This study seeks the technological knowledge of English teachers at Bukittinggi City in learning. This research used descriptive qualitative research because it explores and describes the ability of Technological Knowledge for English teachers. The participants of this study were the teachers and the students in Bukittinggi City. The selecting of participants used purposive sampling techniques and the selection of students used the accidental sampling method. The instruments were a questionnaire given to teachers and students, and semi-structured interviews. Then the supporting data was the lesson plan sent by a representative from the interviewee. In analyzing the questionnaire used quantitative method. For the teacher's questionnaire, the results are in the form of an average and then categorize their technological knowledge. And then, the students’ questionnaires obtained results in the form of percentages. Then for the lesson plan, use the document review method and the restatement interview from what was said. The findings of the research in the knowledge and application of technological knowledge has begun to be applied. However, most teachers’ abilities and skills in technological knowledge were in the average category. Therefore, the understanding and utilization of technological knowledge for English Vocational High School teachers must be expanded further in designing lesson plans, teaching and learning processes, and assessing the students.